(untitled) (Brazilian Journal of Oceanography, 2011)
Side-scan sonar observations conducted at Mito artificial habitat site in the southwest coast off Taiwan, documented the locations of both concrete cubic blocks (more than 10,000 units) and scrapped steel boats (39 units) deployed previously. Based on their geographic locations, the concrete cubic artificial reefs could be grouped into 14 reef sets. About 30% of the reefs were deployed out of the promulgated site area. For the purpose of artificial habitat site identification and fishery resources management, a database structure was designed to accommodate types and positions of reefs, information of reef sets, bathymetric contours, textures of bottom sediments and geomorphological characteristics. The effectiveness of Mito artificial habitat site was evaluated to be positive after the deployment of both concrete block reefs and steel boat reefs.